2013
DOI: 10.11604/pamj.2013.15.97.2524
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of first line highly active antiretroviraltherapy on serum selenium, cd4 count and body mass index: a short cross sectional and prospective study

Abstract: IntroductionThe relationship that exists between body weights, serum selenium and immunological markers of HIV/AIDS continue to provoke more researches in the recent times. The objectives of this study were to examine baseline body mass index, CD4 count and serum selenium and to prospectively assess the impacts of HAART on same parameters 48 weeks post HAART among HIV patients.MethodsA cohort comprising 140 newly diagnosed HIV positive were prospectively studied. Anthropometric measurements, serum selenium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
4
6
0
Order By: Relevance
“…This was evident by a significant higher (P<0.05) mean±SD HAART serum Vitamin A, Vitamin C, Vitamin E, Zinc, Selenium, Potassium and Sodium serum levels (except Copper and Chloride) of the HIV positive Patients in comparison with the mean±SD Pre-HAART values. This observation agrees with that of Akinola et al [21], Arinola et al [47] and Sundaram et al [73] who observed a significant increase in zinc and that of Akinboro et al [22] and Look et al [74] who observed a significant increase…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was evident by a significant higher (P<0.05) mean±SD HAART serum Vitamin A, Vitamin C, Vitamin E, Zinc, Selenium, Potassium and Sodium serum levels (except Copper and Chloride) of the HIV positive Patients in comparison with the mean±SD Pre-HAART values. This observation agrees with that of Akinola et al [21], Arinola et al [47] and Sundaram et al [73] who observed a significant increase in zinc and that of Akinboro et al [22] and Look et al [74] who observed a significant increase…”
Section: Discussionsupporting
confidence: 92%
“…Micronutrients which comprise of essential trace elements (e.g Zinc, Copper and Selenium) and vitamins (e,g Vitamin A, C and E) are nutrients needed in minute specific quantities in the body which play leading roles in the production of enzymes, hormones and other substances, helping to regulate growth activity, essential in wound healing, development and the functioning of the immune and reproductive system, maintenance of the integrity of skin and mucous membranes, which also function as a barrier to bacteria and viruses and protection against lipid peroxidation among several others [20][21][22][23]. Most micronutrients are not generated in the body but are derived from food intake [24][25][26].…”
Section: Effects Of Highly Active Antiretroviral Therapy (Haart) On Some Serum Micronutrients and Electrolytesmentioning
confidence: 99%
“…Thus, it is difficult to directly compare studies using different selenium status readouts [ 143 ]. Anti-retroviral therapies may also confound the selenium status [ 144 , 145 ]. However, some studies have not supported this notion [ 146 ].…”
Section: Immune Responses To Pathogensmentioning
confidence: 99%
“…Weight gain following ART initiation is well documented . However, the weight gain on ART is likely to follow a prior weight loss.…”
Section: Introductionmentioning
confidence: 99%